An analysis of endometrial bleeding patterns in perimenopausal women - Indrani, Mukhopadhyay; P. S., Rao; S., Nataraj; Biswas, Manash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Perimenopause is the period surrounding menopause characterized by ovulatory dysfunction and menstrual irregularities. Taking into consideration the importance of perimenopause and its consequences, we decided to study this topic in order to know the different menstrual irregularities in relation to age, the spectrum of endometrial histopathology, in relation to various gynaecological conditions as per the PALMCOEIN classification of AUB. Methods: The study population comprised of 100 women in the age group of 40- 59 years who reported to our tertiary care centre of Armed Forces for evaluation of abnormal uterine bleeding. The study was a community based cross - sectional descriptive study. Patients were examined, using one of the three techniques – Dilatation and curettage, suction aspiration and hysteroscopy and endometrial biopsy. Results: Out of the 100 women evaluated for perimenopausal bleeding, heavy menstrual bleeding was the commonest in 53% cases. The maximum no. of cases was in 40-44-year age group (57.44 %). The clinical diagnosis of fibroid uterus was found in 45% cases, AUB (O) in 36% cases, AUB (Polyp) in 8% cases, AUB (Adenomyosis) in 9% cases and AUB (Malignancy) in 2% cases. On endometrial curettage, proliferative type of endometrium was found in 43% cases, secretory type in 18% cases and hyperplasia was found in 37% cases. Out of 2 cases of atypical hyperplasia 1 case each (50%) was found in the age group of 50-54 years and 55-59 years, respectively. Conclusions: In the present study, there was good correlation between abnormal uterine bleeding, clinical diagnosis and histopathological findings.